Empowering novice academics for student success workbook : wearing different hats - Hugo, J. (Johann), 1954- (SUN MeDIA, 2021)
The preparation for a career in education and training cuts into all three categories of knowledge: cognitive, affective, and psychomotor, and all four dimensions of competence. The implication is that effective teaching requires not only theoretical knowledge, but also practical abilities that include a range of instructional skills and techniques. The workbook therefore contains a number of activities intended to promote professional competence.